Automação 4.0 de Prensa Extrusora e Aplicação Energética em Óleo e Torta de Crambe - Lewandoski, Cristiano Fernando (2019)
The objective of this study was to evaluate the mechanical pressing process of crambe grains "Crambe abyssinica Hochst" at different temperatures and speeds of rotation in a mechanical extruder with automation 4.0. The experimental design was used to determine the effects of these 4 × 5 parameters. The experimental design was developed with four temperatures (110-120 ° C, 120-30 ° C, 130-140 ° C and 140-150 ° C) and five rotation speeds [1000, 1200, 1400, 1600 and 1800 RPM (Rotation per minute)]. The physicochemical properties of the oil and the bromatological properties of the cake were evaluated. The physico-chemical properties of the oil and bromatológicas of the crambe pie are affected by the extraction at different temperatures and rotation of the extruder. The quality parameters of the specific mass oil, viscosity, the bromatological crude fiber, lipids and moisture of the crambe pie were larger with extraction temperature of 140-150 ℃. The oil yield was benefited by the extraction with temperature of 140-150 ℃ and rotation of 1800 RPM. Oil yield increased 56% as temperature went from 110-120 ° C to 140-150 ° C and 41% when RPM increased from 1000 to 1800 RPM. Protein and ash content of crambe pie decreased with increasing temperature and RPM. The crude fiber, lipids and moisture of the crambe pie were larger with rotation of 1800 RPM